2021
DOI: 10.1186/s12889-021-10618-x
|View full text |Cite
|
Sign up to set email alerts
|

Driver-passenger communicative stress and psychological distress among Chinese bus drivers: the mediating effect of job burnout

Abstract: Background This study aimed to investigate the relationship between driver-passenger communicative stress and psychological distress among bus drivers, as well as whether job burnout mediates the effect of driver-passenger communicative stress on psychological distress. Methods A questionnaire consisting of a 12-item version of the General Health Questionnaire (GHQ-12), a one-item driver-passenger communicative stress scale, the Maslach Burnout Inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 54 publications
0
6
0
1
Order By: Relevance
“…5. Questionário de estressores ocupacionais: elaborado, para o presente estudo, com base na literatura sobre estressores em motoristas de transporte coletivo de passageiros (Lámbarry et al, 2016;Tse & Flin, 2006;Oliveira & Pinheiro, 2007;Silve & Zavarize, 2017;Tu et al, 2021;Zanelato & Oliveira, 2008). Este possui 12 itens, que avaliam: condições ambientais (alagamentos, enchentes); condições da estrada (buracos, falta de sinalizações); condições ergonômicas da cabine; relacionamento motorista-cobrador (conflitos); relacionamento com passageiros (reclamações); relacionamento com fiscais da empresa (pressões); escala de trabalho; pressão do tempo para cumprimento do trajeto; possibilidades de assalto e roubos; congestionamentos no trânsito; acidentes (medo de se envolver em um); motociclistas e cliclistas (que não seguem normas de trânsito).…”
Section: Instrumentosunclassified
“…5. Questionário de estressores ocupacionais: elaborado, para o presente estudo, com base na literatura sobre estressores em motoristas de transporte coletivo de passageiros (Lámbarry et al, 2016;Tse & Flin, 2006;Oliveira & Pinheiro, 2007;Silve & Zavarize, 2017;Tu et al, 2021;Zanelato & Oliveira, 2008). Este possui 12 itens, que avaliam: condições ambientais (alagamentos, enchentes); condições da estrada (buracos, falta de sinalizações); condições ergonômicas da cabine; relacionamento motorista-cobrador (conflitos); relacionamento com passageiros (reclamações); relacionamento com fiscais da empresa (pressões); escala de trabalho; pressão do tempo para cumprimento do trajeto; possibilidades de assalto e roubos; congestionamentos no trânsito; acidentes (medo de se envolver em um); motociclistas e cliclistas (que não seguem normas de trânsito).…”
Section: Instrumentosunclassified
“…Satisfied drivers, such as bus drivers, are generally more willing to comply with work safety procedures, which can result in lower accident rates than dissatisfied drivers [ 2 ]. There were two deadly traffic accidents in China in 2018 and 2020, which were caused by drivers deliberately driving their buses into a river, both of which resulted in significant casualties [ 3 ]. Although it was difficult to determine the reasons for these intentional actions, Chinese transportation enterprise management is seeking to improve their employees’ job satisfaction [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, more evidence is needed to explore the relationship between procedural justice and job satisfaction, for example, in the group of bus drivers. Because bus drivers in China suffer from driver-passenger communicative stress [ 3 ], any lack of interaction fairness could seriously affect their job satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Taking the perspective of the job demand-resource theory, Bakker and de Vries (2021) found that job burnout of high-tech workers could reduce their happiness and improve their turnover intention. And studies have explored the direct relationship between job burnout and job performance within a particular occupational group, such as teachers (Peng et al, 2019), nurses (Li et al, 2022), and drivers (Tu et al, 2021), and have failed to consider such issue among more broader groups, such as new generation of employees, and also ignored the antecedent effect of the implicit variable of psychological contract breach on employees' job burnout.…”
Section: Introductionmentioning
confidence: 99%